(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
Deforestation causes environmental degradation. Awareness of the people might have influence on reduction of deforestation. The main purposes of the study were to determine the farmers’ awareness regarding deforestation and to explore relationship between the selected characteristics of the farmers and their awareness. The study was conducted to only one village namely Raingamari (The project village of Khulna University) of Jalma union under Batiaghata upazila of Khulna district. Data were collected from 53 family heads of the village on their 10 selected characteristics such as age, educational qualification, farming experience, family size, farm size, family income, organizational participation, cosmopoliteness, extension media contact, training exposure. Data were also collected on farmers’ awareness regarding deforestation. Data were collected from the respondents during April to July 2017 through personal interview using a pretested interview schedule. Most of the respondents were highly aware of deforestation. The respondents showed highest level of awareness regarding “deforestation causes greenhouse effect which consequently increase the average temperature of the earth” while they were less aware regarding “deforestation threatens the livelihoods and cultural integrity of people that depend on forest”. Among the 10 selected characteristics of the respondents, educational qualification, organizational participation, extension media contact showed positive significant relationships with their awareness regarding deforestation while only the annual income had the negative significant relationship with their awareness regarding deforestation. Res. Agric., Livest. Fish.6(2): 193-202, August 2019